1956
DOI: 10.1113/jphysiol.1956.sp005453
|View full text |Cite
|
Sign up to set email alerts
|

Adrenaline and noradrenaline in human plasma during natural sleep

Abstract: Little is known at present about the physiology of sleep. The proximity of centres which probably control sleep and wakefulness with centres of autonomic activity suggests a functional connexion. We have therefore investigated the effect of natural sleep on the concentration of catechol amines in plasma. METHODSTwo or three blood samples were collected from each subject, the first during sleep, the second 5-10 min. later when the subject was awake and the third on the following morning before breakfast. The fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

1957
1957
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 9 publications
1
8
0
1
Order By: Relevance
“…Detailed, multiple sampling studies of 24-hour plasma levels of E and DA have not been previously reported, but a number of reports have suggested the existence of circadian rhythm of plasma and urinary £18, 19,22,24 T n e detectability of a diurnal rhythm of plasma E level in the aged and its obvious relation to the 24-hour cycle blood pressure levels suggest that at least some inherent chronobiological functions related to sympathetic outflow are preserved in the elderly. The reason for the dichotomy between the nocturnal decline in plasma E levels, MAP, and heart rate and the persistent high NE levels ( Figure 5) is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed, multiple sampling studies of 24-hour plasma levels of E and DA have not been previously reported, but a number of reports have suggested the existence of circadian rhythm of plasma and urinary £18, 19,22,24 T n e detectability of a diurnal rhythm of plasma E level in the aged and its obvious relation to the 24-hour cycle blood pressure levels suggest that at least some inherent chronobiological functions related to sympathetic outflow are preserved in the elderly. The reason for the dichotomy between the nocturnal decline in plasma E levels, MAP, and heart rate and the persistent high NE levels ( Figure 5) is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary excretion of catecholamine metabolites has been observed to be higher during the day than at night. 16 " 19 Several investigative groups have reported a diurnal variation in plasma NE levels and noted a significant fall in NE levels during sleep in recumbent young normotensive 13 ' ' *• 2O " 22 and hypertensive subjects.…”
Section: Essential Hypertension • Catecholamines Norepinephrine • Epimentioning
confidence: 99%
“…Virtually all the studies reported so far have involved urinary measurement of epinephrine and norepinephrine levels, although methods have been available for measuring plasma catecholamine levels for more than 10 years and were applied successfully to human studies as early as 1955 by Renton and Weil-Malherbe, who reported that plasma epinephrine levels were higher during the waking state than during sleep. 94 Several factors may account for this relative lack of studies of plasma catecholamine responses to psychological stimuli and this problem will be discussed in more detail later. An important factor in our own laboratory has been some early experimental observations on normal subjects in which 2 successive 25-ml.…”
Section: Plasma Catecholamine Studiesmentioning
confidence: 99%
“…In addition, difficulties in the methods of collection, storage and measurement of the catecholamines in blood have led investigators to conclude that there is much 'noise', but no circadian variability in plasma norepinephrine [I], This is unlikely in light of the pronounced circadian rhythms found in epinephrine and norepinephrine by several other investigators, including Von Euler et at. [59], Cession-Fossion et al [ 12], Karkl [30], Petosse and Soulairac [46], Renton and Weil-Malherbe [51] and Reinberg et al [50], Reinberg et al compared the effects of (a) normal diurnal activity and regular uncontrolled diet with (b) complete 36-hour bed rest and a hypocaloric diet every 4 h. on urinary adrenaline (epinephrine) and nor adrenaline (norepinephrine), heart rate and blood pressure in normal healthy man. They found that the curves for adrenaline and noradrenaline closely paralleled those for pulse and blood pressure under both experimental condi tions.…”
Section: Pressorsmentioning
confidence: 99%